Climatic shifts, geomorphic change, ancient routes of migration and adaption in southwestern China: Site formation processes at Luojiaba, Sichuan Province. Issue 3 (18th December 2022) - Zhang, Junna; Storozum, Michael J.; Chen, Weidong; Rao, Zongyue; Hamilton, Rebecca; Zheng, Zhexuan; Chen, Zhiyao; Yu, Xuetong; Xia, Zhengkai
Abstract: Archaeologists frequently invoke climate change as a driving cause for ancient expansions of human populations, but geomorphic changes can also play an important role in opening or closing routes of migration. In China, archaeological evidence demonstrates that valleys in the Jialing River's watershed were important routes for the movement of Neolithic populations from the catchments of the Yellow River to the Yangtze River. Here, we examine how fluvial geomorphological regime shifts may have also influenced the migration pathways and adaptive strategies of Neolithic people into the Sichuan Basin by using a combination of sedimentological and palynological analysis at Luojiaba, an archaeological site located on one of the eastern tributaries of the Jialing River. The results show that people settled on seasonally stable landforms, including the Zhonghe River floodplain at Luojiaba (5300–4800 cal. B.P.). They carried out fishing and hunting activities on the front edge of the floodplain close to the river channel and built dwelling features on the higher ground at the back edge of the floodplain, which was not affected by seasonal floods. We hypothesize that during the Holocene Climatic Optimum before 5500 cal. B.P., high water levels as well as severe surface erosion caused by a strong East Asian Summer Monsoon (EASM) blocked pathways into the upper reaches of the Jialing River watershed. Only after a series of cold, dry climate events driven by a decrease in EASM intensity ca. 5500–5000 cal. B.P. did water levels recede significantly. This allowed alluvial aggradation to occur, which created floodplains and terraces along the valley that may have opened a new route for the migration into the Sichuan Basin. Our results reveal the human–environment dynamics surrounding Luojiaba in the uplands of southwestern China and highlight the impact of coupled climatic‐geomorphic regime shifts on human settlement and subsistence strategies, across both space and time.